Assessing the efficacy of perilymphatic fistula repair surgery in alleviating vestibular symptoms and associated auditory impairments - Matsuda, Han; Hornibrook, Jeremy; Ikezono, Tetsuo (Frontiers in Neurology, 2023)
Perilymph Fistula (PLF), abnormal communication between the fluid-filled space of the inner ear and the air-filled space of the middle ear, is a significant cause of vestibular and auditory symptoms. This is a retrospective study of 22 cases treated with PLF repair surgery, selected based on our surgical indication. We analyzed the characteristics of these 22 cases and evaluated the efficacy of PLF repair surgery in treating vestibular and auditory symptoms. Cases with antecedent events had significantly shorter intervals before surgery. The postoperative recovery from vestibular symptoms following PLF repair surgery was strikingly rapid, with 82% of cases demonstrating marked improvement within a week, even in chronic cases. Despite the notable absence of a control group in the study, the marked improvements in vestibular symptoms and substantial reductions in Dizziness Handicap Inventory (DHI) scores suggest that the observed benefits are attributable to the surgical intervention. Further, timely surgery showed improvements in hearing, with some benefits also seen in late-stage surgeries. Using the perilymph-specific protein Cochlin-tomoprotein (CTP) as a diagnostic biomarker, we could prove that PLF could be responsible for disequilibrium and related auditory disturbances in these patients. A new hypothesis is proposed that the chronic disequilibrium experienced by many PLF patients is due to enhanced mobility of the utricle and not to endolymphatic hydrops. Further research is needed to fully elucidate PLF’s symptoms and treatment efficacy using the surgical indication we developed.